2018
DOI: 10.1016/j.hpb.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatoduodenectomy after Roux-en-Y gastric bypass: technical considerations and outcomes

Abstract: Pancreatic surgeons will see an increasing number of patients with Roux-en-Y anatomy who will require evaluation and resection for periampullary diseases. For PD after RYGB, we recommend remnant gastrectomy with reconstruction using the BP limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Although the incidence cholangiocarcinoma post bariatric surgery appeared low, the three reported cases of cholangiocarcinoma were diagnosed at an advanced stage (Beghdadi, 2020). Cases by Tumour Type 3,[24][25][26][27][28]31 of the 24 cases. These were distributed as follow; Pain (4), Pain and Jaundice (3), Jaundice and Weight loss (1), Jaundice (1), and Incidental finding (4).…”
Section: Cholangiocarcinomamentioning
confidence: 97%
See 3 more Smart Citations
“…Although the incidence cholangiocarcinoma post bariatric surgery appeared low, the three reported cases of cholangiocarcinoma were diagnosed at an advanced stage (Beghdadi, 2020). Cases by Tumour Type 3,[24][25][26][27][28]31 of the 24 cases. These were distributed as follow; Pain (4), Pain and Jaundice (3), Jaundice and Weight loss (1), Jaundice (1), and Incidental finding (4).…”
Section: Cholangiocarcinomamentioning
confidence: 97%
“…The review found 11 authors that reported pancreatic and cholangiocarcinoma with total 27 reported cases 3,19,[22][23][24][25][26][27][28][29][30][31] .…”
Section: Reported Cases Post Bariatric Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies describe the operative experience for pancreatic adenocarcinoma or biliary strictures in these patients, with fate of the remnant gastrectomy and management of the biliopancreatic limb being key considerations. [30][31][32][33] Given the long duration between RYGB and symptom development, more RYGB patients will likely be referred to hepatobiliary centers for management of benign and malignant biliary disease in the coming years, despite the decreasing frequency of RYGB being performed for morbid obesity.…”
Section: Access Techniques and Outcomesmentioning
confidence: 99%